Corrosion-resistant and wear-resistant sealing ring and preparation method thereof

Through the formulation of core-shell structure aluminum-based composite particles and gradient functional material, combined with molded vulcanization and electrophoretic deposition technology, the seal ring structure is optimized, and the contradiction between corrosion resistance and wear resistance of seal ring is solved, and high corrosion resistance, wear resistance and self-repair functions are achieved, meeting the long-term and stable operation needs of industrial equipment under complex working conditions.

CN120484314APending Publication Date: 2025-08-15HAINING JIACHENG RUBBER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510642865.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

Existing seal rings are difficult to take into account both corrosion resistance and wear resistance, and cannot meet the high requirements of modern industry for the comprehensive performance of seal rings.

Method used

The core-shell structure aluminum-based composite particles and gradient functional material formula is adopted. The inner layer uses fluoroelastomer and core-shell particles to improve corrosion resistance. The outer layer uses polydopamine and nanodiamond particles to improve wear resistance. The structure is optimized through molded vulcanization, pulsed electrophoresis deposition and thermal medium filling, combining ultrasonic vibration and self-healing functions.

Benefits of technology

It realizes the high corrosion resistance, wear resistance and self-repair functions of the seal ring under complex working conditions, reduces equipment maintenance costs and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120484314A_ABST
    Figure CN120484314A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant and wear-resistant sealing ring and a preparation method thereof. The preparation method comprises the steps of core-shell structure aluminum-based composite particle preparation, inner and outer layer raw material preparation, sealing ring structure forming, outer layer coating treatment and the like. The sealing ring is made of an inner layer material and an outer layer material in specific parts by weight, the inner layer contains fluororubber, core-shell particles and the like, and the outer layer contains a polydopamine solution, nano-diamond particles and the like; and the outer layer contains hexagonal boron nitride nanosheets, nano-diamond particles, a microcapsule repairing agent and the like. The prepared sealing ring combines various materials to realize high wear resistance and a self-repairing function, maintains corrosion resistance, has excellent corrosion resistance and wear resistance, good thermal conductivity and the self-repairing function, effectively solves the problems of thermal resistance of the outer boron nitride coating and rigidity of the inner rubber compared with the prior art, remarkably improves the comprehensive performance, and is suitable for large-scale popularization and application. And the use requirements of various industrial devices under complex working conditions are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of seal manufacturing, in particular to a corrosion-resistant and wear-resistant sealing ring and a preparation method thereof. Background Art

[0002] In many industrial fields, such as chemical, petroleum, and machinery manufacturing, seals are key components that ensure the sealing performance of equipment. Their performance directly impacts the operational stability, safety, and service life of the equipment. As industrial production evolves toward high-precision, high-load, and complex operating conditions, the requirements for seals' corrosion and wear resistance are becoming increasingly stringent. However, existing seals present numerous difficult-to-overcome technical challenges in coping with these complex operating conditions.

[0003] In terms of improving the corrosion resistance of sealing rings, the traditional approach is usually to use corrosion-resistant materials or add anti-corrosion additives. For example, using fluoropolymer coatings or adding anti-corrosion fillers such as metal oxides to the rubber matrix. However, these methods are often accompanied by negative effects. Although fluoropolymer coatings can block the erosion of corrosive media to a certain extent, the coating is hard and brittle. When the sealing ring is subjected to friction, the coating is prone to cracking and falling off, which accelerates the damage of the sealing ring and causes a significant decrease in wear resistance. Adding metal oxide anti-corrosion fillers will change the internal structure of the rubber, reducing its flexibility. When it is frequently opened and closed or subjected to mechanical vibration, the rubber matrix is prone to cracking, which not only affects the wear resistance but may also cause the seal to fail.

[0004] From the perspective of improving wear resistance, common methods are to increase the hardness of the rubber or add high-hardness wear-resistant particles. However, simply increasing the hardness of the rubber will reduce its elasticity and flexibility, resulting in the inability of the seal ring to fit tightly against the sealing surface, reducing the sealing effect and weakening the seal ring's adaptability to different working conditions. Adding high-hardness wear-resistant particles, such as ordinary silicon carbide particles, can improve the surface hardness to a certain extent, but the interfacial bonding between these particles and the rubber matrix is insufficient. During high-speed friction, the particles easily fall off from the matrix, not only failing to continuously exert their wear-resistant effect, but also forming new wear sources on the surface of the seal ring, exacerbating the degree of wear.

[0005] Existing technologies have difficulty in achieving both corrosion resistance and wear resistance in sealing rings, and are unable to meet the high comprehensive performance requirements of modern industry. Therefore, it is necessary to provide a sealing ring and its preparation method that can achieve both corrosion resistance and wear resistance, as well as synergistic optimization of other comprehensive properties. Summary of the Invention

[0006] The purpose of the present invention is to provide a corrosion-resistant and wear-resistant sealing ring and a preparation method thereof, so as to solve the shortcomings of existing sealing rings in corrosion resistance and wear resistance, and at the same time optimize their comprehensive performance, including improving sealing effect, enhancing thermal conductivity, and imparting self-repair function, etc., to meet the needs of long-term stable operation of industrial equipment under complex working conditions, reduce equipment maintenance costs, and extend equipment service life.

[0007] To achieve the above object, the present invention provides the following technical solutions: A first aspect of the present invention provides a method for preparing a corrosion-resistant and wear-resistant sealing ring, comprising the following steps: (1) Preparation of core-shell structured aluminum-based composite particles Aluminum powder is placed in a boric acid solution, and a passivation layer is formed on the surface of the aluminum powder through anodization. Using electrochemical principles, a dense aluminum oxide (Al2O3) film is formed on the surface of the aluminum powder, which prevents further oxidation of the aluminum. The presence of the passivation layer improves the corrosion resistance of the aluminum powder. Hexagonal boron nitride (h-BN) nanosheets are coated on the surface of the passivation layer to form core-shell particles. The dried core-shell particles are used for mixing with the inner layer materials. The h-BN nanosheets have good lubricity, high temperature resistance and chemical stability. The core-shell structure formed by coating the surface of the aluminum powder not only further enhances the corrosion resistance of the particles, but also gives the particles special physical and chemical properties, which is conducive to the subsequent compounding with other materials.

[0008] (2) Functionally gradient material formulation configuration Inner layer material: Fluororubber (FKM) is mixed with core-shell particles, graphene, a silane coupling agent, and a liquid rubber plasticizer. Fluororubber (FKM), with its excellent corrosion, high-temperature, and oil resistance, is the primary base material for the seal ring. The core-shell particles enhance the material's hardness, wear, and corrosion resistance. Graphene, with its high conductivity, strength, and lubricity, further enhances the material's mechanical properties and wear resistance. The silane coupling agent improves the interfacial bonding between the inorganic particles and the rubber matrix, while the liquid rubber plasticizer enhances the rubber's flexibility and processing properties.

[0009] Outer layer material: Mix polydopamine (PDA) solution with h-BN nanosheets, nano-diamond particles, and microcapsule repair agent; polydopamine (PDA) solution has good adhesion and can be used as a binder to bond h-BN nanosheets, nano-diamond particles, and microcapsule repair agent together. Nano-diamond particles have high hardness and can significantly improve the wear resistance of the outer layer. Under certain conditions, the microcapsule repair agent can release the repair agent to repair damage to the material surface.

[0010] The inner layer material is made into a semi-finished film, and the outer layer material is transferred to the coating equipment; by rationally configuring the components of the inner and outer layer materials, the sealing ring has a gradient function, the inner layer has good corrosion resistance and certain mechanical properties, and the outer layer has excellent wear resistance and self-repairing function, which improves the overall comprehensive performance of the sealing ring.

[0011] (3) Gradient structure molding of sealing ring Inner Layer Forming: The semi-finished film is compression-vulcanized to form the seal ring substrate. The substrate surface is then polished and cleaned. Through compression vulcanization, the fluororubber and other additives undergo a cross-linking reaction under high temperature and pressure, forming a seal ring substrate with a defined shape and properties. Grinding and cleaning the substrate surface removes impurities and unevenness, creating a favorable surface condition for the outer coating. Compression vulcanization creates a stable three-dimensional network structure in the inner layer, improving the mechanical properties and dimensional stability of the seal ring.

[0012] Outer Coating: Pulsed electrophoretic deposition is used to form a porous BN coating on the surface of the seal ring substrate. After coating, the seal ring proceeds directly to the next step. Under the influence of an electric field, charged particles such as h-BN nanosheets migrate to the surface of the seal ring substrate and deposit to form a porous BN coating. The porous BN coating has a certain porosity, which facilitates the subsequent filling of the thermal conductive medium. It also increases the bonding area between the coating and other outer layer materials, improving the overall bonding strength.

[0013] (4) Optimization of thermal conductivity and wear resistance The pores of the porous BN coating formed in step (3) are filled with a heat-conducting medium; the pores of the porous BN coating are filled with a heat-conducting medium, heat-conducting silicone oil, and the good heat-conducting properties of the silicone oil are utilized to improve the heat-conducting properties of the sealing ring and reduce the temperature rise during use. The filling of the heat-conducting silicone oil improves the heat dissipation capacity of the sealing ring and helps to extend the service life of the sealing ring.

[0014] The outer coating formed in step (3) is coated with nano-diamond particles to strengthen the wear-resistant layer through physical intercalation or chemical bonding; the nano-diamond particles are coated on the coating surface and are firmly attached to the coating surface through physical intercalation or chemical bonding to form a strengthened wear-resistant layer. The wear-resistant layer formed by the nano-diamond particles further improves the wear resistance of the outer layer of the sealing ring, making it better able to resist friction and wear.

[0015] (5) Interface enhancement and self-repair function integration Ultrasonic vibration is applied during the compression vulcanization process in step (3) to promote interlayer bonding; the mechanical vibration of ultrasound can promote the diffusion and mixing of molecules between the layers and enhance the interfacial bonding between the inner and outer layer materials.

[0016] A hydrophobic film is prepared on the surface of the BN coating formed in step (4). A polytetrafluoroethylene (PTFE) hydrophobic film is prepared on the surface of the BN coating by atomic layer deposition (ALD). The thickness of the hydrophobic film can be precisely controlled using ALD technology. PTFE has low surface energy and good hydrophobicity, which can prevent corrosive media from penetrating into the coating. When the microcapsule repair agent encounters high temperature or other triggering conditions, the capsule wall material ruptures, releasing epoxy resin and imidazole catalysts. The epoxy resin undergoes a curing reaction under the action of the catalyst, repairing the damage to the material surface. The preparation of the hydrophobic film improves the corrosion resistance and water resistance of the sealing ring. The microcapsule repair agent gives the sealing ring a self-repairing function, which can extend the service life of the sealing ring to a certain extent and reduce the cost of maintenance and replacement.

[0017] Preferably, in step (1), the BN nanosheets of the core-shell particles are prepared by CVD method, the precursors are BCl3 and NH3, and the reaction temperature is 900-1100°C; The diameter of the aluminum powder is 5-10 μm, the concentration of the boric acid solution is 0.1-0.3 mol / L, the thickness of the Al2O3 passivation layer is 5-10 nm, and the thickness of the h-BN nanosheet is 0.1-0.3 μm.

[0018] Preferably, in step (2), in the inner layer material, the content of core-shell particles is 12-15 wt%, the content of graphene is 2-5 wt%, the content of silane coupling agent is 0.5-1 wt%, and the content of liquid rubber plasticizer is 3-5 wt%.

[0019] Preferably, in step (2), the outer layer material contains 5-8 wt% of nano-diamond particles and 3-5 wt% of microcapsule repair agent. The nano-diamond particles have a particle size of 50-100 nm and are surface-modified with a silane coupling agent (KH560).

[0020] Preferably, in step (2), the microcapsule repair agent comprises epoxy resin and imidazole catalyst, the capsule wall material is melamine formaldehyde resin, and the microcapsule distribution density is 10 6 -10 7 / cm³, and the release temperature of the repair agent is 80-120℃.

[0021] Preferably, in step (2), the nano-diamond particles are used to improve the wear resistance of the outer layer of the sealing ring, and at the same time, they need to be well combined with other materials of the outer layer to ensure the overall performance. Conventional surface modification methods for nano-diamond particles mostly use silane coupling agents alone, which is difficult to fully meet the complex functional requirements of the sealing ring. Therefore, the nano-diamond particles are modified using the following method: Polydopamine pretreatment: Disperse the nanodiamond particles in a Tris buffer solution (pH 8.5) containing 0.1-1.0 wt% polydopamine and stir at 25-40°C for 12-24 hours to allow the polydopamine to evenly coat the surface of the nanodiamond particles. Silane coupling reaction: adding a silane coupling agent to the dispersion obtained in the above step, controlling the concentration of the silane coupling agent to 0.5-2.0 mol / L, and continuing the reaction at a temperature of 40-80°C for 2-6 hours to chemically bond the silane coupling agent to the polydopamine coating and the hydroxyl groups on the surface of the nanodiamond; Post-treatment: The product obtained in the above step is centrifuged (8000-12000 r / min, 10-20 min), washed with deionized water 3-5 times, and then vacuum dried at 60-100°C for 12-24 hours.

[0022] In this modification method, polydopamine (PDA) exhibits strong adhesion and can form a durable coating on a variety of surfaces. It is combined with a silane coupling agent, allowing the polydopamine to adhere to the surface of the nanodiamond particles. The silane coupling agent then reacts with the polydopamine and the active groups on the nanodiamond particle surfaces. This method enhances the interfacial bonding between the nanodiamond particles and the outer layer materials, such as the polydopamine solution and hexagonal boron nitride nanosheets, preventing them from separating during use and ensuring stable performance of their respective functions. Furthermore, it optimizes the surface properties of the nanodiamond particles, further enhancing their wear resistance, ensuring effective resistance to friction under complex operating conditions and reducing wear on the seal.

[0023] Preferably, in step (3), the voltage of the pulse electrophoretic deposition is 80-120 V, the deposition time is 5-10 minutes, the duty cycle is 20-40%, the coating thickness is 15-25 μm, and the porosity is 25-35%.

[0024] Preferably, in step (4), the heat-conducting medium is thermal silicone oil, with a thermal conductivity of 0.14 W / (m·K), a pore filling rate of ≥90%, a kinematic viscosity of 50-100 mm² / s (25°C), and a contact angle with the BN coating of ≤30°.

[0025] Preferably, in step (5), the temperature of the compression vulcanization is 140-160° C., the pressure is 10-15 MPa, and the time is 15-20 minutes.

[0026] Preferably, in step (5), the ultrasonic frequency is 20-40 kHz, and the hydrophobic membrane is a PTFE hydrophobic membrane (with a thickness of 20-50 nm).

[0027] Preferably, in step (5), a 20-50 nm thick polytetrafluoroethylene (PTFE) hydrophobic film is prepared on the surface of the BN coating by atomic layer deposition (ALD).

[0028] A second aspect of the present invention provides a corrosion-resistant and wear-resistant sealing ring, which is prepared from the following raw materials in parts by weight: The inner layer material (total weight 100 parts) includes: 70-80 parts of fluororubber (FKM), 12-15 parts of core-shell particles, 2-5 parts of graphene (sheet diameter 1-5 μm), 0.5-1 part of silane coupling agent (KH560), and 3-5 parts of liquid rubber plasticizer (dioctyl phthalate); Wherein, the core-shell particles further include: Core: Aluminum powder with a diameter of 5-10μm, with the aluminum powder core accounting for 75-85%; Shell: 0.1-0.3 μm thick h-BN nanosheets, with the h-BN shell accounting for 15-25%; The outer layer material (total weight 100 parts) includes: 60-70 parts of polydopamine (PDA) solution, PDA concentration of 5-8wt%, 20-30 parts of h-BN nanosheets (sheet diameter 1-3μm), 5-8 parts of modified nanodiamond particles (particle size 50-100nm), 3-5 parts of microcapsule repair agent, thermal conductive silicone oil (accounting for 90-95% of the pore volume of the outer layer coating), and polytetrafluoroethylene (PTFE) 20-50nm thick (prepared by ALD); Among them, the microcapsule repair agent further includes: Wall material: melamine formaldehyde resin; Core material: epoxy resin (80-90wt%) + imidazole catalyst (10-20wt%).

[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares aluminum-based composite particles with a core-shell structure, whose passivation layer and coated nanosheets improve corrosion resistance and facilitate composite properties; the inner layer is based on fluororubber, and a variety of ingredients are added to balance corrosion resistance with certain mechanical and wear-resistant properties; the outer layer uses polydopamine as a binder, and a combination of multiple materials achieves high wear resistance and self-repairing functions while maintaining corrosion resistance. In terms of preparation technology, ultrasonic vibration is applied during mold vulcanization to enhance the interlayer bonding force, and pulse electrophoretic deposition is used to form a porous BN coating. Nano-diamond particles are subsequently applied to strengthen the wear-resistant layer and prepare a PTFE hydrophobic film to improve corrosion resistance. In terms of structural optimization, the porosity of the porous BN coating is precisely controlled, and it is used to capture abrasive particles and fill thermal conductive media to improve wear resistance and thermal conductivity. A gradient structure design is adopted, so that the inner layer focuses on corrosion resistance and the outer layer focuses on wear resistance and self-repairing. The division of labor and cooperation achieve a good balance between the two properties under complex working conditions, thereby improving the overall performance of the sealing ring.

[0030] 2. The present invention optimizes the thermal conductivity of the sealing ring by filling the pores of the porous BN coating with thermally conductive silicone oil, which can effectively reduce the temperature increase during use, avoid the degradation of material properties due to excessive temperature, and further ensure the reliability of the sealing ring.

[0031] 3. The present invention uses a microcapsule repair agent to release epoxy resin and imidazole catalysts for curing and repair when damaged, thereby enhancing the self-repairing ability of the sealing ring, reducing sealing failure caused by accumulation of minor damage, and reducing maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a line graph showing comparative test results of thermal conductivity of the embodiments and comparative examples of the present invention; Figure 2 The figure is a line graph showing the comparative test results of the wear rates of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0033] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0034] Example 1: A method for preparing a corrosion-resistant and wear-resistant sealing ring provided in an embodiment of the present invention comprises the following steps: (1) Preparation of core-shell aluminum-based composite particles: Aluminum powder is placed in a boric acid solution, and a passivation layer is formed on the surface of the aluminum powder by anodization; and hexagonal boron nitride (h-BN) nanosheets are coated on the surface of the passivation layer to form core-shell particles. The dried core-shell particles are used for mixing with the inner layer materials.

[0035] The BN nanosheets of the core-shell particles were prepared by CVD method, with BCl3 and NH3 as precursors and a reaction temperature of 1000°C; the diameter of the aluminum powder was 8μm, the concentration of the boric acid solution was 0.2mol / L, the thickness of the Al2O3 passivation layer was 8nm, and the thickness of the h-BN nanosheet was 0.2μm.

[0036] (2) Preparation of inner and outer layer materials: Fluororubber (FKM) is mixed with core-shell particles, graphene, silane coupling agent, and liquid rubber plasticizer to form the inner layer material; polydopamine (PDA) solution is mixed with h-BN nanosheets, nanodiamond particles, and microcapsule repair agent to form the outer layer material. The inner layer material is made into a film semi-finished product to prepare the sealing ring substrate, and the outer layer material is transferred to the coating equipment as the outer coating of the sealing ring substrate.

[0037] The inner layer material contains 13wt% core-shell particles, 4wt% graphene, 0.8wt% silane coupling agent, and 4wt% liquid rubber plasticizer. The outer layer material contains 6wt% nanodiamond particles and 4wt% microcapsule repair agent. The nanodiamond particles are 78nm in size and have been surface-modified with a silane coupling agent (KH560).

[0038] More preferably, the microcapsule repair agent in this embodiment comprises epoxy resin and imidazole catalyst, the capsule wall material is melamine formaldehyde resin, and the microcapsule distribution density is 10 6 -10 7 / cm³, and the release temperature of the repair agent is 80-120℃.

[0039] (3) Gradient structure formation of the sealing ring: The semi-finished film is molded and vulcanized to form the sealing ring substrate. The substrate surface is polished and cleaned, and a porous BN coating is formed on the surface of the sealing ring substrate using pulse electrophoretic deposition technology. The coated sealing ring directly enters the next step. Specifically, in this embodiment, the pulse electrophoretic deposition voltage is 100V, the deposition time is 8 minutes, the duty cycle is 30%, the coating thickness is 20μm, and the porosity is 30%.

[0040] In this embodiment, the temperature of compression vulcanization is 150° C., the pressure is 12 MPa, and the time is 18 min. Ultrasonic vibration is applied during the compression vulcanization process to promote interlayer bonding.

[0041] (4) External coating treatment: To further enhance the thermal conductivity of the sealing ring, a porous BN coating is formed on the surface of the sealing ring substrate in this embodiment, and the pores are filled with a thermally conductive medium. Preferably, a 30 nm thick polytetrafluoroethylene (PTFE) hydrophobic film is deposited on the surface of the BN coating by atomic layer deposition (ALD) in this embodiment to enhance the waterproof performance.

[0042] In practice, nano-diamond particles are coated on the surface of the outer coating formed on the sealing ring, and the wear-resistant layer can be strengthened by physical intercalation or chemical bonding to improve the wear resistance of the sealing ring.

[0043] In this embodiment, the heat-conducting medium is thermally conductive silicone oil with a thermal conductivity of 0.14 W / (m·K) and a pore filling rate of ≥90%. The kinematic viscosity of the thermally conductive silicone oil is 50-100 mm² / s (25°C), and the contact angle with the BN coating is ≤30°.

[0044] In this embodiment, the surface of the nano-diamond particles is modified by a silane coupling agent, and the modification steps are as follows: a) Polydopamine pretreatment: Nanodiamond particles were dispersed in a buffer solution containing 0.5 wt% polydopamine and stirred at 30°C for 20 hours to allow the polydopamine to evenly coat the surface of the nanodiamond particles. b) Silane coupling reaction: adding a silane coupling agent to the dispersion obtained in step a, controlling the concentration of the silane coupling agent to 1.0 mol / L, and continuing the reaction at 55°C with stirring for 4 hours to allow the silane coupling agent to chemically bond with the polydopamine coating and the hydroxyl groups on the surface of the nanodiamond; c) Post-treatment: The product obtained in step b was centrifuged, washed four times with deionized water, and then dried in vacuo at 80°C for 18 hours.

[0045] The corrosion-resistant and wear-resistant sealing ring prepared by the embodiment of the present invention achieves comprehensive optimization of material properties through multi-step synergistic enhancement. During the preparation stage of the core-shell structure aluminum-based composite particles, an Al2O3 passivation layer is generated on the surface of the aluminum powder by anodizing with a boric acid solution. The corrosion resistance of the aluminum powder is improved by electrochemical principles. Then, h-BN nanosheets are coated on the surface of the passivation layer by CVD to enhance the comprehensive performance of the particles, laying the foundation for subsequent material composite. In the gradient functional material formulation configuration stage, the inner layer is based on fluororubber as the matrix, with core-shell particles, graphene, etc. added. The corrosion resistance of fluororubber, as well as the core-shell particles and graphene, are used to improve the material hardness and wear resistance. Silane coupling agents enhance interfacial bonding, and liquid rubber plasticizers improve processing performance. The outer layer uses polydopamine as the binder, combined with nanodiamond particles and microcapsule repair agents, to give full play to the high hardness of nanodiamonds and the self-healing properties of microcapsule repair agents. The resulting gradient structure gives the sealing ring diverse functions.

[0046] In addition, when the gradient structure of the sealing ring is formed, compression vulcanization allows the inner layer material to cross-link to form a stable matrix, and pulse electrophoretic deposition is used to construct a porous BN coating on the surface of the matrix, which not only stabilizes the inner layer structure but also creates conditions for subsequent processing. During the thermal conductivity and wear resistance optimization process, thermal conductive silicone oil is filled to improve the heat dissipation capacity. Based on the good thermal conductivity of silicone oil, the operating temperature is reduced; nano-diamond particles are coated to strengthen the wear-resistant layer by physical or chemical means to enhance the surface wear resistance. In the stage of integrating interface enhancement and self-repair functions, ultrasonic vibration is applied during compression vulcanization, and mechanical vibration is used to promote the diffusion of molecules between layers and enhance the interlayer bonding force; atomic layer deposition technology is used to prepare a PTFE hydrophobic film on the surface of the BN coating. With its low surface energy, it prevents the penetration of corrosive media. The microcapsule repair agent releases repair components under specific conditions to self-repair the damage and extend the service life of the sealing ring.

[0047] In addition, an embodiment of the present invention also provides a corrosion-resistant and wear-resistant sealing ring, which is prepared from the following raw materials in parts by weight: The inner layer material (total weight 100 parts) includes: 76 parts of fluororubber (FKM), 14 parts of core-shell particles, 3 parts of graphene (sheet diameter 1-5 μm), 0.8 parts of silane coupling agent (KH560), and 4 parts of liquid rubber plasticizer (dioctyl phthalate); Wherein, the core-shell particles further include: Core: Aluminum powder with a diameter of 5-10μm, with the aluminum powder core accounting for 80%; Shell: 0.2 μm thick h-BN nanosheet, h-BN shell accounts for 20%; The outer layer material (total weight 100 parts) includes: 65 parts of polydopamine (PDA) solution, PDA concentration 6wt%, 25 parts of h-BN nanosheets (sheet diameter 1-3μm), 6 parts of modified nanodiamond particles (particle size 50-100nm), 4 parts of microcapsule repair agent, thermal conductive silicone oil (accounting for 90-95% of the pore volume of the outer layer coating), and 30nm thick polytetrafluoroethylene (PTFE) (prepared by ALD). Among them, the microcapsule repair agent further includes: Wall material: melamine formaldehyde resin; Core material: epoxy resin (85wt%) + imidazole catalyst (15wt%).

[0048] Example 2: The preparation method of this embodiment is basically the same as that of Example 1, with the only difference being: In step (1) of this embodiment, the aluminum powder diameter is 10 μm, the boric acid solution concentration is 0.3 mol / L, the Al2O3 passivation layer thickness is 10 nm, and the h-BN nanosheet thickness is 0.3 μm. In addition, the CVD preparation conditions are changed to use BCl3 and NH3 as precursors, and the reaction temperature is 1100°C.

[0049] In step (2) of this embodiment, the inner layer material (total weight 100 parts) includes the following components in parts by weight: fluororubber (FKM): 80 parts, core-shell particles: 15 parts, graphene (sheet diameter 5 μm): 5 parts, silane coupling agent (KH560): 1 part, and liquid rubber plasticizer (dioctyl phthalate): 5 parts.

[0050] The outer layer material (total weight 100 parts) includes the following components in parts by weight: polydopamine (PDA) solution (concentration 8wt%): 70 parts, h-BN nanosheets (sheet diameter 3μm): 30 parts, modified nanodiamond particles (particle size 100nm): 8 parts and microcapsule repair agent: 5 parts.

[0051] In this embodiment, the filling rate of the thermal conductive silicone oil is 95%.

[0052] In this embodiment, the modification of nano-diamond particles includes the following steps: a) Polydopamine pretreatment: 1.0 wt% PDA solution, stirred at 40 °C for 24 h; b) Silane coupling reaction: the concentration of silane coupling agent was 2.0 mol / L, and the reaction was carried out at 80°C for 6 hours; c) Post-treatment: washing with deionized water for 5 times and vacuum drying at 100°C for 24 hours.

[0053] In step (3) of this embodiment, the molding vulcanization conditions are: temperature 160° C., vulcanization pressure 15 MPa, vulcanization time 20 min, and ultrasonic vibration frequency 40 kHz.

[0054] The relevant parameters of pulse electrophoretic deposition are: pulse voltage 120V, electrophoretic deposition time 10 minutes, and duty cycle 40%.

[0055] In this embodiment, the thickness of the porous BN coating is 25 μm and the porosity is 35%.

[0056] In step (4) of this embodiment, the thermal conductivity of the thermally conductive silicone oil is 0.16 W / (m·K), the kinematic viscosity is 100 mm² / s (25°C), and the PTFE hydrophobic film is prepared by ALD, and the thickness of the hydrophobic film is 50 nm.

[0057] Example 3: The preparation method of this embodiment is basically the same as that of Example 1, with the only difference being: In step (1) of this embodiment, the aluminum powder diameter was 5 μm, the boric acid solution concentration was 0.1 mol / L, the Al2O3 passivation layer thickness was 5 nm, and the h-BN nanosheet thickness was 0.1 μm. In addition, the CVD preparation conditions were changed to use BCl3 and NH3 as precursors, and the reaction temperature was 900°C.

[0058] In step (2) of this embodiment, the inner layer material (total weight 100 parts) includes the following components in parts by weight: fluororubber (FKM): 70 parts, core-shell particles: 12 parts, graphene (sheet diameter 1 μm): 2 parts, silane coupling agent (KH560): 0.5 parts, and liquid rubber plasticizer (dioctyl phthalate): 3 parts.

[0059] The outer layer material (total weight 100 parts) includes the following components in parts by weight: polydopamine (PDA) solution (concentration 4wt%): 60 parts, h-BN nanosheets (sheet diameter 1μm): 20 parts, modified nanodiamond particles (particle size 100nm): 5 parts and microcapsule repair agent: 3 parts.

[0060] In this embodiment, the filling rate of the thermal conductive silicone oil is 90%.

[0061] In this embodiment, the modification of nano-diamond particles includes the following steps: a) Polydopamine pretreatment: 0.1 wt% PDA solution, stirred at 25 °C for 12 h; b) Silane coupling reaction: the concentration of silane coupling agent is 0.5 mol / L, and the reaction temperature is 40°C for 2 hours; c) Post-treatment: washing with deionized water for 3 times and vacuum drying at 60° C. for 24 hours.

[0062] In step (3) of this embodiment, the molding vulcanization conditions are: temperature 140° C., vulcanization pressure 10 MPa, vulcanization time 15 min, and ultrasonic vibration frequency 20 kHz.

[0063] The relevant parameters of pulse electrophoretic deposition are: pulse voltage 80 V, electrophoretic deposition time 6 minutes, and duty cycle 20%.

[0064] In this embodiment, the thickness of the porous BN coating is 15 μm and the porosity is 25%.

[0065] During the use of sealing rings, there is a significant contradiction between wear resistance and corrosion resistance. From the perspective of traditional improvement methods, in terms of improving corrosion resistance, although fluoropolymer coatings can resist corrosion, they are hard and brittle, and are prone to cracking and falling off during friction, reducing wear resistance. Adding metal oxide anti-corrosion fillers will change the rubber structure, reduce flexibility, and easily crack when mechanical vibration or frequent opening and closing occurs, affecting wear resistance and possibly causing seal failure. When improving wear resistance, increasing the hardness of the rubber will reduce its elasticity and flexibility, reducing the sealing effect and adaptability to working conditions. Adding ordinary high-hardness wear-resistant particles will easily fall off during high-speed friction due to insufficient interfacial bonding with the rubber matrix, forming a new wear source that exacerbates wear and may also damage the rubber structure and reduce corrosion resistance. From the nature of the material, the high-hardness components or structures required for wear resistance will destroy the stable protective film required for corrosion resistance, causing corrosion. In the process of performance optimization, the treatment method that focuses on one performance often has a negative impact on another performance, making it difficult to strike a balance.

[0066] In Examples 1-3, in order to solve the above technical problems, core-shell aluminum-based composite particles are prepared, and their passivation layer and coated nanosheets improve corrosion resistance and facilitate composite properties; the inner layer is based on fluororubber, and a variety of ingredients are added to take into account corrosion resistance and certain mechanical and wear resistance. The outer layer uses polydopamine as a binder, and a combination of multiple materials achieves high wear resistance and self-repairing functions while maintaining corrosion resistance. In terms of preparation technology, ultrasonic vibration is applied during mold vulcanization to enhance the interlayer bonding force, pulse electrophoresis deposition forms a porous BN coating, and nano-diamond particles are subsequently coated to strengthen the wear-resistant layer and prepare a PTFE hydrophobic film to improve corrosion resistance. In terms of structural optimization, the porosity of the porous BN coating is precisely controlled, and it is used to capture abrasive particles and fill thermal conductive media to improve wear resistance and thermal conductivity. A gradient structure design is adopted, so that the inner layer focuses on corrosion resistance and the outer layer focuses on wear resistance and self-repairing. The division of labor and cooperation achieve a good balance of the two properties under complex working conditions, thereby improving the overall performance of the sealing ring.

[0067] In addition, the porosity of the porous BN coating has many effects on the performance of the sealing ring. When the porosity is between 25% and 35%, on the one hand, the pores can capture abrasive particles. During the friction process, the abrasive particles entering the coating will be blocked by the pores, preventing them from sliding further on the surface of the sealing ring and causing greater wear, thereby improving the wear resistance. On the other hand, the pores provide space for subsequent filling of thermal conductive media, which is beneficial to improving thermal conductivity. From a process perspective, the use of pulsed electrophoretic deposition technology can accurately control the porosity of the coating, and precise control of the porosity can be achieved by adjusting parameters such as voltage, deposition time, and duty cycle.

[0068] Furthermore, an outer coating pore filling rate of ≥90% allows the thermally conductive medium to fully utilize its properties. When this filling rate reaches this standard, the thermally conductive medium forms continuous heat conduction channels within the coating pores, greatly improving thermal conductivity. For example, thermally conductive silicone oil, due to its excellent thermal conductivity, can effectively transfer heat within the coating through a high filling rate. From a structural perspective, a high filling rate allows the thermally conductive silicone oil to be tightly packed within the pores, reducing the presence of low-thermal-conductivity media such as air and avoiding poor heat conduction due to air barriers. Furthermore, a high filling rate also helps enhance the coating's structural stability, reducing the problem of reduced coating strength due to excessive pores, and ensuring the stable performance of the sealing ring's thermal conductivity and wear resistance properties over long-term use.

[0069] Comparative Example 1: Uncoated structure optimization: Using a 20μm dense BN coating, thermal conductivity decreased by 15%. In wear resistance testing, the wear rate was twice that of Example 1.

[0070] In addition, the inner layer is made of ordinary rubber with a Shore hardness of 60A, which affects the sealing performance. The outer layer has no nano-diamond particles and a hardness of HV400, which causes severe wear.

[0071] Comparative Example 2: Inadequate coating structure optimization: The porous BN coating with a porosity of 20% had a thermal conductivity of 320.028 W / (m·K) after being filled with silicone oil. The wear resistance was not significantly improved, and the wear rate was 30% higher than that of Example 1.

[0072] In addition, the inner layer has a 20% core-shell structure and 2wt% plasticizer, with a Shore hardness exceeding 80A, which affects dynamic adaptability. Although nano-diamond particles are added to the outer layer, the overall performance is poor.

[0073] Comparative Example 3: Incorrect coating structure optimization: A porous BN coating with a porosity of 40% had a thermal conductivity of 240.056 W / (m·K) after being filled with silicone oil. The coating's structural strength decreased, and it easily fell off during wear testing.

[0074] In addition, the inner layer has a 10% core-shell structure and 6wt% plasticizer, a thermal conductivity of 3.0W / (m·K), and a Shore hardness of 65A. The outer layer contains 10% nano-diamond particles, making the coating brittle.

[0075] Comparative Example 4: No coating structure optimization was performed: With the untreated BN coating, the thermal conductivity decreased significantly and the wear amount was more than three times that of Example 1.

[0076] In addition, the inner layer is made of conventional rubber with a Shore hardness of 65-75A and a thermal conductivity of 2.5W / (m·K). The outer layer does not contain nano-diamond particles and has a low hardness.

[0077] Comparative Example 5: The coating structure optimization was substandard: The porosity of the porous BN coating fluctuated between 25% and 35%, and the thermal conductivity was unstable. The wear resistance was inconsistent, with some areas experiencing severe wear.

[0078] In addition, the inner core-shell structure and plasticizer ratio are inappropriate, resulting in a Shore hardness of 72-78A and a thermal conductivity of 3.2-3.8W / (m·K). The outer layer contains 4%-6% nano-diamond particles and has a hardness of HV550-HV650, making the overall performance unstable.

[0079] Comparative Example 6: Incorrect coating optimization method: Drilling holes on the dense BN coating reduces the effective thermal conductivity to around 200W / (m・K). The holes are easily worn and have poor wear resistance.

[0080] In addition, the inner layer has 8wt% plasticizer and 8% core-shell structure, with a Shore hardness below 60A and easy deformation. The outer layer does not have reasonable addition of nano-diamond particles, which impairs the overall performance.

[0081] Thermal conductivity experimental data of the above embodiments and comparative examples: comparison group Inner layer thermal conductivity (W / (m・K)) Outer layer effective thermal conductivity (W / (m・K)) Overall thermal conductivity reduction Example 1 3.6 280 30% Example 2 3.7 278 30.5% Example 3 3.55 282 29.5% Comparative Example 1 2.8 340 15% Comparative Example 2 3.2 320.028 20% Comparative Example 3 3.0 240.056 40% Comparative Example 4 2.5 340 15% Comparative Example 5 3.3 275 35% Comparative Example 6 2.9 200 50% Thermal conductivity analysis of the sealing rings prepared by this invention: The examples, through coating structure optimization, construct a porous BN coating and fill it with thermally conductive silicone oil, resulting in a stable outer layer with an effective thermal conductivity of approximately 280 W / (m·K), and an overall thermal conductivity reduction of around 30%. In contrast, the comparative examples, due to inappropriate coating structure and material ratio design, have either excessively high thermal conductivity reductions (40% in Comparative Example 3 and 50% in Comparative Example 6), or excessively low inner layer thermal conductivity (only 2.5 W / (m·K) in Comparative Example 4).

[0082] The wear resistance test data of the above embodiments and comparative examples are as follows: comparison group Wear rate (mg / h) Relative wear rate multiple of Example 1 Example 1 5 1 Example 2 4.8 0.96 Example 3 4.6 0.92 Comparative Example 1 10 2 Comparative Example 2 6.5 1.3 Comparative Example 3 8 1.6 Comparative Example 4 12 2.4 Comparative Example 5 6.5 1.3 Comparative Example 6 15 3 Analysis of the wear resistance of the sealing rings prepared by the present invention: The examples, leveraging a pore-captured abrasive particle mechanism and nanodiamond particle reinforcement, maintained a wear rate of 4.6-5 mg / h. However, due to the lack of effective wear-resistant design, the comparative examples exhibited significantly higher wear rates, reaching as high as 10 mg / h in comparative example 1 and 15 mg / h in comparative example 6, respectively, double and triple those of example 1.

[0083] Shore hardness test data of the above embodiments and comparative examples: comparison group Inner layer Shore hardness Outer layer hardness (HV) Example 1 70A 600 Example 2 70A 600 Example 3 70A 600 Comparative Example 1 60A 400 Comparative Example 2 82A 550 Comparative Example 3 65A 650 Comparative Example 4 72A 400 Comparative Example 5 76A 600 Comparative Example 6 58A 500 Shore hardness analysis of the sealing rings prepared by this invention: The Example stabilizes the inner layer's Shore hardness at 70A, ensuring dynamic adaptability. The outer layer, incorporating nanodiamond particles, achieves a hardness of HV600, enhancing wear resistance. In the Comparative Examples, the hardness of some inner layers deviates from the appropriate range, with the inner layer in Comparative Example 2 exceeding 80A, affecting dynamic adaptability. The hardness of some outer layers is insufficient, with the outer layer in Comparative Example 1 reaching only HV400, indicating poor wear resistance.

[0084] Combined with the above experimental data, the present invention optimizes the stiffness of the inner rubber layer by adding materials such as core-shell particles to fluororubber, thereby effectively improving the wear resistance while ensuring a certain degree of flexibility to achieve a good sealing effect. The stiffness of the inner rubber layer has an important impact on the wear resistance of the sealing ring. The existing inner rubber stiffness is usually low. When subjected to friction, the rubber is prone to large deformation and cannot effectively resist the friction force, resulting in increased wear. For example, under frequent mechanical vibration or high-speed friction conditions, low-rigidity rubber will experience surface tearing, peeling, and other phenomena, shortening the service life of the sealing ring. Properly increasing the stiffness of the inner rubber layer can enhance its ability to resist friction deformation, reduce material loss caused by friction, and thus improve wear resistance.

[0085] Furthermore, the sealing ring of the present invention exhibits an improved outer layer effective thermal conductivity. For example, by filling the pores of the porous BN coating with thermally conductive silicone oil, heat can be rapidly transferred away, reducing the operating temperature of the sealing ring, slowing material aging, maintaining the stability of the various properties of the sealing ring, and extending its service life. This improved outer layer effective thermal conductivity is closely related to solving the heat dissipation problem of the sealing ring under complex operating conditions. In actual use, the sealing ring generates heat due to friction. If heat is not dissipated in a timely manner, the temperature will continue to rise. Excessively high temperatures accelerate the aging of the rubber material, degrading its physical properties, and thus affecting the sealing performance, corrosion resistance, and wear resistance of the sealing ring.

[0086] In general, the coating structure optimization and gradient modulus design proposed in the present invention have achieved remarkable results in balancing thermal conductivity and wear resistance, effectively solving the problems of thermal resistance of the outer BN coating and stiffness of the inner rubber layer, and greatly improving the overall performance of the sealing ring compared with the comparative example.

[0087] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

Claims

1. A method for preparing a corrosion-resistant and wear-resistant sealing ring, characterized in that: The following steps are involved: (1) Preparation of core-shell structured aluminum-based composite particles Aluminum powder is placed in a boric acid solution to form a passivation layer, and hexagonal boron nitride nanosheets are coated on the surface of the passivation layer to form core-shell particles. The dried core-shell particles are used for mixing with the inner layer material; (2) Preparation of inner and outer layer raw materials Inner layer material: Mix fluororubber with core-shell particles, graphene, silane coupling agent, and liquid rubber plasticizer; Outer layer material: Mix polydopamine solution with hexagonal boron nitride nanosheets, nanodiamond particles, and microcapsule repair agent; The inner layer material is made into a semi-finished film, and the outer layer material is transferred to the coating equipment; (3) Sealing ring structure molding Inner layer molding: mold and vulcanize the semi-finished film to form the sealing ring matrix, and polish and clean the matrix surface; Outer layer coating: a porous boron nitride coating is formed on the surface of the sealing ring substrate by using pulse electrophoretic deposition technology to obtain a sealing ring coated with an outer layer coating; (4) External coating treatment The pores of the porous boron nitride coating formed in step (3) are filled with a thermal conductive medium, and then nano-diamond particles are coated on the surface of the outer coating.

2. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 1, characterized in that: In step (1), the hexagonal boron nitride nanosheets are prepared by chemical vapor deposition, with boron trichloride and ammonia being selected as starting materials.

3. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 1, characterized in that: In step (1), the thickness of the Al2O3 passivation layer is 5-10 nm, and the thickness of the hexagonal boron nitride nanosheets is 0.1-0.3 μm.

4. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 1, characterized in that: The surface of the nano-diamond particles is modified by a silane coupling agent, and the modification steps are as follows: a) Polydopamine pretreatment: Disperse the nanodiamond particles in a buffer solution containing 0.1-1.0 wt% polydopamine and stir at 25-40°C for 12-24 hours to allow the polydopamine to evenly coat the surface of the nanodiamond particles. b) Silane coupling reaction: adding a silane coupling agent to the dispersion obtained in step a, controlling the concentration of the silane coupling agent to be 0.5-2.0 mol / L, and continuing the reaction at a temperature of 40-80°C for 2-6 hours with stirring to allow the silane coupling agent to chemically bond with the polydopamine coating and the hydroxyl groups on the surface of the nanodiamond; c) Post-treatment: The product obtained in step b is centrifuged, washed with deionized water for 3-5 times, and then vacuum dried at 60-100° C. for 12-24 hours.

5. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 1, characterized in that: In step (2), the microcapsule repair agent contains epoxy resin and imidazole catalyst, the capsule wall material is melamine formaldehyde resin, and the release temperature of the repair agent is 80-120°C.

6. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 1, characterized in that: In step (3), the temperature of the compression vulcanization is 140-160°C, the pressure is 10-15 MPa, the time is 15-20 min, and ultrasonic vibration is applied during the compression vulcanization process; The thickness of the porous boron nitride coating is 15-25 μm and the porosity is 25-35%.

7. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 1, characterized in that: In step (4), the heat-conducting medium is thermal silicone oil, and the pore filling rate of the outer coating layer is ≥90%.

8. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 7, characterized in that: In step (4), a hydrophobic film is prepared on the coating surface.

9. The method for preparing a corrosion-resistant and wear-resistant sealing ring according to claim 8, characterized in that: A 20-50 nm thick polytetrafluoroethylene hydrophobic film was prepared on the coating surface by atomic layer deposition.

10. A corrosion-resistant and wear-resistant sealing ring prepared according to any one of claims 1 to 9, characterized in that: It is prepared from the following raw materials in parts by weight: 100 parts of inner layer material: including 70-80 parts of fluororubber, 12-15 parts of core-shell particles, 2-5 parts of graphene, 0.5-1 part of silane coupling agent, and 3-5 parts of liquid rubber plasticizer; The graphene sheet diameter is 1-5 μm, and the liquid rubber plasticizer is dioctyl phthalate; Wherein, the core-shell particles further include: Core: 75-85% aluminum powder core; Shell: 15-25% hexagonal boron nitride nanosheet shell; 100 parts of outer layer material: including 60-70 parts of polydopamine solution, 20-30 parts of hexagonal boron nitride nanosheets, 5-8 parts of modified nano-diamond particles, 3-5 parts of microcapsule repair agent, and thermal conductive silicone oil accounting for 90-95% of the pore volume of the outer layer coating; Among them, the microcapsule repair agent further includes: Wall material: melamine formaldehyde resin; Core material: 80-90wt% epoxy resin and 10-20wt% imidazole catalyst.

Citation Information

Patent Citations

  • Method for hydrophobic and oleophobic modification of surface of separation membrane

    CN104524985A

  • Core-shell structure particle of fluorine-containing polymer modified micro-nano aluminum powder and preparation method of core-shell structure particle

    CN115716129A

  • Composite core-shell structure nano-powder and preparation method thereof

    CN118812970A

  • Super-amphiphobic coating with durable wear resistance and corrosion resistance on surface of aluminum alloy and preparation method of super-amphiphobic coating

    CN119463629A